Low-cost membranes for submerged membrane bioreactors - Gander, Michelle (Cranfield University, 2000)
The present work aims to assess the feasibility of using an ostensibly low-cost polypropylene (PP) material for processing municipal wastewater from the University sewage works. Two different types of hydrophilic membranes were employed, both being macroscopically homogenous (i.e. isotropic) in their physical nature. These were: • An extruded polymeric membrane (EPP) containing microscopic glass beads as a fibrulating agent (0.5 jam pore size), and • A non-woven felt of microscopic fibres (NWPP) of 1.5, 3 and 5 jam pore size. The membrane materials were mounted on plate and frame modules and used in a submerged membrane bioreactor (MBR) run at 0.06 bar, fed continuously with primary effluent. Membrane performance was assessed in terms of specific flux and rejection, the latter with respect to indicator bacteria. Overall bioreactor performance was measured in terms of BOD5 and COD removal and the extent of nitrification. An initial economic analysis was also undertaken to identify major costs in treating municipal wastewater with the two configurations of MBR. Analysis of these two areas concluded that: • flux decline is most significant in the first few hours of filtration, • bacterial rejection increases with the formation of the dynamic membrane, • organics removal is high even when mixed liquor suspended solids are low, • sludge production is reduced due to long solids retention times and substrate inhibited microorganisms, and • economics point to submerged MBRs being more cost efficient than side-stream MBRs due to their lower operating costs. Only one NWPP membrane (5 jum pore size) could be concluded to be suitable for use to treat municipal wastewater, and only if disinfection was not required. The other NWPP membranes where highly susceptible to fouling, therefore producing a permeate flux unacceptable for commercial treatment processes. The PS membrane showed the most suitable characteristics for treatment of municipal wastewater in submerged MBRs.